Depressive symptoms and substance use: Changes overtime among a cohort of HIV-positive and HIV-negative MSM. (1st February 2020) - Javanbakht, Marjan; Shoptaw, Steven; Ragsdale, Amy; Brookmeyer, Ron; Bolan, Robert; Gorbach, Pamina M.
Highlights: Frequent heroin and methamphetamine users had the highest prevalence of depressive symptoms. Compared to other substances, methamphetamine was the most influential predictor of depressive symptoms. Declines in depressive symptoms overtime noted for most drugs, except for methamphetamine users who showed no change overtime. Abstract: Background: The objective of this study was to examine depressive symptoms overtime and quantify the variance in symptoms attributable to substance use among a cohort of HIV-positive and HIV-negative men. Methods: Participants were enrolled in an NIH/NIDA funded cohort, with 534 men resulting in 1, 888 visits between August 2014 and June 2018. Participants were between 18 and 45 years, and half were HIV-positive. At baseline and semi-annual visits, information was collected on depressive symptoms, sexual behaviors, and substance use. Changes overtime in symptom scores were evaluated using individual growth curve modeling. Results: The average CES-D20 score was 19.5 (SD = 12.7). Depressive symptoms were highest among daily/weekly methamphetamine users (56% vs. 39% occasional users and 27% non-users; p value<.01). Factors independently associated with depressive symptoms included methamphetamine use (adjusted OR = 1.5; 95% CI 1.1–2.3) and transactional sex (adjusted OR = 1.8; 95% CI 1.4–2.5). Based on growth curve modeling, methamphetamine was the most influential predictor of depressive symptoms, accounting for 10% of individual variance (p value<.01). Declines in depressive symptoms were noted for heavy users of a number of drugs, except for methamphetamine. For instance, those reporting daily/weekly heroin had a 3.38 point decline in CESD20 scores overtime (p value = 0.01). However, heavy methamphetamine users had much higher CESD20 scores and their scores remained high overtime (p value for change = 0.91). Conclusions: The prevalence of depressive symptoms among this cohort of HIV-negative and HIV-positive MSM was high, especially among frequent methamphetamine users. These findings suggest that reducing methamphetamine use may have the potential to reduce depressive symptoms.